Trail of Adventure Tourism of Senior Generation - Mohammad Fakhruddin Mudzakkir; Roy Setiawan; Sanju Khuma Singh Singh; Ahmad Fauzi (MBR (Management and Business Review), 2018)
The main aim of this research is to explore what factor that determines of senior generation doing adventure tourism. More specifically in this study, not all ages were studied but only in the old generation. Using case study and data collection used interview techniques. There were two participants who were interviewed by both participants aged > 50 years and had done more than 20 times doing trail adventure activities. This research used snowball sampling techniques. Overall there are five identifiable factors related to factors that drive senior generation to do trail adventure activities: maintaining healthy body, strengthening brotherhood, returning to nature and nostalgia.